2017
DOI: 10.1037/abn0000293
|View full text |Cite
|
Sign up to set email alerts
|

Faces and facets: The variability of emotion recognition in psychopathy reflects its affective and antisocial features.

Abstract: Psychopathy consists of a constellation of affective-interpersonal features including lack of empathy, callousness, manipulativeness and interpersonal charm, impulsiveness and irresponsibility. Despite its theoretical and predictive value in forensic contexts, the relationships between the psychometric dimensions of psychopathy, including its antisocial features, and the construct's neuropsychological characteristics remain uncertain. In this study, 685 personality-disordered prisoners with histories of seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 113 publications
2
15
2
Order By: Relevance
“…This was significant in zero-order correlations, but not when controlling for age and IQ. This positive trend is contrary to hypotheses and inconsistent with prior findings (e.g., Igoumenou, Harmer, Yang, Coid, & Rogers, 2017). However, with a different task of OFC functioning, the Iowa Gambling Task, Hughes et al (2015) found psychopathy, and the antisocial facet specifically, to be positively associated with performance.…”
Section: Discussioncontrasting
confidence: 99%
“…This was significant in zero-order correlations, but not when controlling for age and IQ. This positive trend is contrary to hypotheses and inconsistent with prior findings (e.g., Igoumenou, Harmer, Yang, Coid, & Rogers, 2017). However, with a different task of OFC functioning, the Iowa Gambling Task, Hughes et al (2015) found psychopathy, and the antisocial facet specifically, to be positively associated with performance.…”
Section: Discussioncontrasting
confidence: 99%
“…However, support for these theories is tempered by an unexpected, positive relationship of callousness, controlling for Boldness and Disinhibition, with accuracy for sad expressions. Although others have reported positive relationships of both interpersonal and antisocial features of psychopathy with accuracy in offender samples (Dargis et al, 2018;Igoumenou et al, 2017), a This document is copyrighted by the American Psychological Association or one of its allied publishers. This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionmentioning
confidence: 99%
“…Although several prominent accounts of psychopathy emphasize difficulties in emotional expression recognition (Blair et al, 2014; Moul, Killcross, & Dadds, 2012), there is some debate as to whether these deficits are particular to emotions signaling another’s distress, most notably fear and sadness, or are more generalized across the emotional spectrum, including, for example, anger, disgust, and happy (Brook & Kosson, 2013; Dawel et al, 2012). The callousness dimension in particular appears to be linked with difficulties recognizing others’ distress from their emotional expressions (Brislin et al, 2018; Dargis, Wolf, & Koenigs, 2018; Gillespie, Mitchell, Satherley, Beech, & Rotshtein, 2015; Igoumenou, Harmer, Yang, Coid, & Rogers, 2017) and is associated with amygdala hypoactivity to fearful facial expressions (Jones, Laurens, Herba, Barker, & Viding, 2009; Viding et al, 2012; White et al, 2012). In contrast, the interpersonal dimension is associated with a pattern of reduced attention to the eyes that is generalized across different emotional expressions (Dargis et al, 2018; Gillespie, Rotshtein, Beech, & Mitchell, 2017; Gillespie, Rotshtein, Wells, Beech, & Mitchell, 2015).…”
mentioning
confidence: 99%
“…This type of inhibitory effect is attenuated if there is an impairment of the general capacity to readily perspective-take, such as in autism spectrum disorder (Chen 2018). In psychopathy, there is a more specific disturbance in relation to certain emotional states of others, such as fearfulness and disgust (Igoumenou 2017). If this disturbance is enduring, as in psychopathy, then more deliberate planning involving explicit focus on the effects of aggression is not inhibited.…”
Section: Elements Of the Violent Mental Statementioning
confidence: 99%